The importance of Ostrom's design principles: Youth group performance in Northern Ethiopia - Stein T. Holden; Mesfin Tilahun (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2017)
Youth unemployment and migration are growing challenges that need more political attention in many countries, particularly countries with rapid population growth and economic transformation. Proactively mobilizing the youth as a resource in the creation of sustainable livelihoods can potentially be a win-win-win solution that Ethiopia is currently attempting with its new youth employment strategy of allocating rehabilitated communal lands to youth groups. This study investigates the extent to which Ostrom's Design Principles (DPs) are adhered to and matter for the early performance of youth groups in terms of their stability, trust and overall performance. We find a high degree of compliance with the Design Principles. From sets of seven DP versus six performance indicators 14 relations were significant and with a sign consistent with the DPs enhancing performance. Three relations were significant but with opposite sign. Some of the DPs appeared more important for early performance of the youth groups. The Ethiopian youth group approach to mobilize landless and unemployed youth is promising and should be tested elsewhere. Further research is needed too on the Ethiopian model as it is still at an early stage of testing as most groups are less than five years old.
Keywords: Q15; Q23; 330; Youth; youth groups; common pool resource management; environmental custodians; collective action; business model; group performanc